Belief in just deserts regarding individuals infected with COVID-19 in Japan and its associations with demographic factors and infection-related and socio-psychological characteristics: a cross-sectional study - Murakami, Michio; Hiraishi, Kai; Yamagata, Mei; Nakanishi, Daisuke; Miura, Asako (PeerJ, 2022)
Prejudice related to the coronavirus disease 2019 (COVID-19) is a social issue worldwide. A possible psychological factor that promotes prejudice is the belief in just deserts (BJD) regarding individuals infected with COVID-19 (i.e., the belief that the infected individual deserves to be infected). The BJD is based on the belief in immanent justice. It is reportedly higher in Japan than in other countries. Therefore, we conducted a cross-sectional study to investigate the BJD among Japanese individuals and clarify its associations with demographic factors or infection-related and socio-psychological characteristics. To this end, we conducted an online questionnaire survey in Japan from August 7–8, 2020, with 1,207 respondents aged 20–69 years. We performed screening to exclude inappropriate responses. We investigated the association between the BJD and demographic factors such as gender and age. We also investigated the association between the BJD and infection-related and socio-psychological characteristics, including risk perception of COVID-19 infection and human rights restrictions (i.e., the degree of agreement with government restrictions on individuals’ behavior during emergencies). Among the surveyed items, human rights restrictions showed a strong association with BJD, followed by risk perception of COVID-19 infection. Men had a slightly higher BJD than women. Our study is significant in that it is the first to investigate the items associated with the BJD, thereby providing foundational information for revising individual perceptions of justice related to COVID-19 and solving prejudice-related issues.
Keywords: Belief in just deserts; Belief in a just world; COVID-19; Human rights restrictions; Prejudice; Risk perception